Analysis of complete Campylobacter concisus genomes identifies genomospecies features, secretion systems and novel plasmids and their association with severe ulcerative colitis. Issue 11 (28th November 2020) - Liu, Fang; Chen, Siying; Luu, Laurence Don Wai; Lee, Seul A.; Tay, Alfred Chin Yen; Wu, Ruochen; Riordan, Stephen M.; Lan, Ruiting; Liu, Lu; Zhang, Li
Abstract : Campylobacter concisus is an emerging enteric pathogen that is associated with several gastrointestinal diseases, such as inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC). Currently, only three complete C. concisus genomes are available and more complete C. concisus genomes are needed in order to better understand the genomic features and pathogenicity of this emerging pathogen. DNA extracted from 22 C . concisus strains were subjected to Oxford Nanopore genome sequencing. Complete genome assembly was performed using Nanopore genome data in combination with previously reported short-read Illumina data. Genome features of complete C. concisus genomes were analysed using bioinformatic tools. The enteric disease associations of C. concisus plasmids were examined using 239 C . concisus strains and confirmed using PCRs. Proteomic analysis was used to examine T6SS secreted proteins. We successfully obtained 13 complete C. concisus genomes in this study. Analysis of 16 complete C. concisus genomes (3 from public databases) identified multiple novel plasmids. pSma1 plasmid was found to be associated with severe UC. Sec-SRP, Tat and T6SS were found to be the main secretion systems in C. concisus and proteomic data showed a functional T6SS despite the lack of ClpV. T4SS was found in 25% of complete C. concisus genomes. This study also found that GS2 strains had larger genomes and higher GC content than GS1 strains and more often had plasmids. In conclusion, this study provides fundamental genomic data for understanding C. concisus plasmids, genomospecies features, evolution, secretion systems and pathogenicity.